Comparing political governance: Southeastern Europe in a global perspective - Brusis, Martin; Thiery, Peter (2006)
Abstract: "The literature on the quality of democracy, market economy and political management in the new democracies of Southeastern Europe has raised three main doubts and concerns. First, democracy in Southeast Europe has turned into power struggles among elites largely isolated from a citizenry that is increasingly disaffected with democracy and susceptible to populist and radical political forces. Second, the institutions of market economy are undermined by the rise of the informal economy and widening social disparities. Third, lacking safe electoral majorities and a sufficiently realistic prospect of EU membership, liberal and Western-oriented political actors have failed to sustain democratic and economic reforms. This paper uses the findings of the Bertelsmann Transformation Index, a global ranking of democracy, market economy and political management, to discuss these hypotheses. We compare the performance profiles for Albania, Bosnia and Herzegovina, Croatia, the Former Yugoslav R